Exploring the status quo of digital accessibility in multinational enterprises - Deitmer, A.; Moehring, M.; Vilas-Boas, J. (EurOMA 2024 Proceedings, 2024)
Digital accessibility (DA) for disabled people is a hot topic, mandatory under UN and EU dispositions. Literature shows a research gap regarding relevant factors that influence the enforcement of DA in Multinationals (MNEs) (RQ1) in order to structure the problem. An exploratory study analysed the current status of DA in MNEs. Findings were consolidated by comparing them with experiences reported by FCEA conference of experts, confirming a notable deficiency in current literature regarding DA status-quo (RQ2). A normative approach, grounded in legal, legitimate, and ethical standards to steer corporate governance in matters of DA was proposed following Soft Systems Methodology.